El rol de Cyrtograpsus angulatus (Crustacea; Brachyura) en los ciclos de vida de Microphallus szidati (Digenea; Microphallidae) y Falsifilicollis chasmagnathi (Acanthocephala; Filicollidae) : Algunos aspectos de su ecología parasitaria - Martorelli, Sergio Roberto (1989)
Based on a study of the larvae from two helminth species parasitizing the crab Cyrtograpsus angulatus Dana, 1851 (Microphallus szidati Martorelli, 1986 and Falsifilicollis chasmagnathi Holcman-Spector et al., 1977), from Mar chiquita lagoom (Argentina) together with the analyses of their life cycles and rates of prevalence, intensity and association coefficient (compared in definitive and intermediate host) the following conclusions have been reached: a) C. angulatus suns to be an excellent intermediate host in the life-cycles of the studied helminths; b) the size of the crabs and the occurrence of natural amputations in the females (Spivak & Politis, in press) appeared correlated with prevalence; c) in the studied crabs the prevalence for F. chasmagnathi is higher in males than in females; d) the intensity did not appear correlated with size and sex of the intermediate host; e) M. szidati and F. chasmagnathi are closely associated with the intermediate host; f) C. angulatus and Himantopus melanurus Vieillot, 1817 (Aves; Recurvirostridae) are reported as new intermediate and definitive hosts, respectively, for F. chasmagnathi; g) Chasmagnathus granulata Dana, 1851 (Crustacea; Brachyura) is reported as a new intermediate host for M. szidati.